The basics of web hacking tools and techniques to attack the web - Pauli, Joshua J. (Syngress is an imprint of Elsevier, 2013)
The Basics of Web Hacking introduces you to a tool-driven process to identify the most widespread vulnerabilities in Web applications. It provides a simple and clean explanation of how to utilize tools such as Burp Suite, sqlmap, and Zed Attack Proxy (ZAP), as well as basic network scanning tools such as nmap, Nikto, Nessus, Metasploit, John the Ripper, web shells, netcat, and more